Online monitoring the hydrolysis of uranium hexafluoride for intermediates by cryogenic layering and FTIR - McNamara, Louis E.; Kelly, John T.; Waldron, Abigail M.; Villa-Aleman, Eliel; Strange Fessler, K. Alicia (Frontiers in Nuclear Engineering, 2023)
Uranium hexafluoride (UF6) is a commonly utilized material feedstock in uranium enrichment processes due to its high vapor pressure and ease of sublimation. When exposed to air, UF6 undergoes spontaneous hydrolysis to form uranyl fluoride (UO2F2) particulates which are utilized for the detection of undeclared nuclear activities by nuclear safeguards organizations. The kinetics of the hydrolysis reaction and how they relate to particle morphology of the product are still debated in the literature. Here, we report the direct, in situ observation of UF6 reaction intermediates by cooling the reaction to cryogenic temperatures to significantly reduce the rate of hydrolysis. The reaction is then observable by Fourier transform infrared (FTIR) spectroscopy. The conversion of UF6 to UOF4 is observed as well as several other bands associated with possible long lived intermediate complexes. Chemometrics are used to further elucidate the reaction pathway from UF6 to UO2F2.